Does Cigarette Smoking Affect Intracytoplasmic Sperm Injection (ICSI) and Embryo Transfer (ET) Outcomes? - Karakoç Sökmensüer, Lale; Esinler, İbrahim; Bozdağ, Gürkan; Aksu, Tarık; Günalp, Serdar (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To investigate the effect of smoking on controlled ovarian stimulation performance and ICSI-ET results. STUDY DESIGN: 193 ICSI cycles with ejaculated sperm were included. ICSI-ET outcome of smokers (n=54) and non-smokers (n=139) were compared. Only initial cycles stimulated via luteal long leuprolide acetate with recombinant follicle stimulating hormone or oral contraceptive plus luteal long leuprolide acetate with rFSH protocol were included. Patients with confounding factors such as female age >40, the presence of any ovarian surgery, unilateral oophorectomy or advanced endometriosis (stage III or more) were excluded. RESULTS: The number of retrieved oocyte cumulus complexes (OCC), metaphase-2 oocytes (M2), the fertilization rate, and the total number of the embryos available on day 3 were comparable among the two groups. Mean number of transferred grade 1, grade 2 and total embryos were also comparable between smokers and non-smokers groups. The cycle cancellation rates due to inadequate response to COH were similar among two groups. The clinical pregnancy rates were not statistically different for the two groups. CONCLUSION: Smoking is a well known poor prognostic factor for spontaneous conception or IVF-ET cycles. However, deleterious effect of smoking may not be directly adapted to the whole ICSI-ET cycles in patients without another risk factor threatening ovarian reserve.